Clinical impact of EUS treatment of walled-off pancreatic necrosis with dedicated devices - Tarantino, Ilaria; Ligresti, Dario; Tuzzolino, Fabio; Barresi, Luca; Curcio, Gabriele; Granata, Antonino; Traina, Mario (Endoscopy International Open, 2017)
Background and study aims Walled-off pancreatic necrosis (WOPN) represents the major risk factor for sepsis-related multiple organ failure. Surgical debridement is an invasive approach associated with high rates of adverse events (AEs) and death. As an alternative, endoscopic ultrasound-guided cysto-gastro-anastomosis has emerged as an effective treatment for WOPNs. Recently a new dedicated-lumen apposing metal stent (LAMS) has been used with satisfactory results in treating peri-pancreatic fluid collections, including WOPNs. The primary outcomes of this study were to evaluate survival and clinical success. Secondary outcomes included: technical success, adverse events and recurrence rate. Patients and methods All consecutive patients with infected WOPN between February 2014 and June 2016 were retrospectively reviewed. Patients underwent placement of a new LAMS incorporated in an electrocautery-enhanced delivery system and direct endoscopic necrosectomy (DEN). DEN was performed immediately after stent deployment and repeated every 3 to 7 days until complete resolution. Results In the study period we treated 20 consecutive patients with infected WOPN using the new LAMS. Technical success was achieved in 95 % of patients. Clinical success was achieved in 73 % and 84.2 % of patients at 1 and 3 months, respectively. Survival rate was 84.2 % and 79 %. Mean length of hospital stay was 19 days (range 3 – 43). No AEs occurred. Patients were followed up after stent retrieval for a mean time of 554,7 days (range 70 – 986) and no recurrence was observed. Conclusions DEN following “1-step, exchange-free” LAMS positioning recorded excellent results. We believe that simplicity of procedure plays a key role in terms of safety.